MANAGING ENDODONTIC EMERGENCY DURING AND BEFORE COVID- 19 LOCKDOWN- A RETROSPECTIVE COMPARATIVE STUDY - Dr. Rakhi Singh; Dr. Arya Gupta; Dr. Vishal; Dr. Dharmendra Kumar Sinha; Dr. Jayaprakash Mugur Basavanna; Dr. Poonam Kumari Jayaprakash (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The rapid spread of coronavirus (COVID-19) has posed substantial test and trials for the entire world especially in case of dentistry and medicine globally. The swiftness and category of response to this virus have been very capricious in terms of different healthcare systems, economies and political ideologies worldwide.1 After the outbreak of Acute Respiratory Disorder Syndrome Corona Virus 2 (SARS-Cov2), or Corona Virus Disease 2019 (COVİD-19), started in China-Wuhan in December 2019, the World Health Organization (WHO) officially announced it as a pandemic on March 12, 2020.2 COVİD-19 mainly transmits through symptomatic or asymptomatic individuals and effectually through breathing. Hence, it has been stated that healthcare workers (HCWs), family members, friends and patients who are in close proximity with COVID-19 patients are at a higher risk of becoming infected or diffusion of the virus.3,4